Change and the 2020 census not whether but how - Cook, Thomas M.; Norwood, Janet Lippe; Cook, Daniel L. (National Academies Press, 2011)
"Sponsored by the Census Bureau and charged to evaluate the 2010 U.S. census with an eye toward suggesting research and development for the 2020 census, the Panel to Review the 2010 Census uses this first interim report to suggest general priorities for 2020 research. Although the Census Bureau has taken some useful organizational and administrative steps to prepare for 2020, the panel offers three core recommendations, and suggests the Census Bureau take and assertive, aggressive approach to 2020 planning rather than casting possibilities purely as hypothetical. The first recommendation on research and development suggests four broad topic areas for research early in the decade. Second, the report suggest that the Bureau take an aggressive, assertive posture toward research in these priority areas. Third, it identifies the setting of bold goals as essential to underscoring the need for serious reengineering and building commitment to change."--Publisher's website.